2021
DOI: 10.1016/j.neuroimage.2020.117433
|View full text |Cite
|
Sign up to set email alerts
|

Associations of quantitative susceptibility mapping with Alzheimer's disease clinical and imaging markers

Abstract: Altered iron metabolism has been hypothesized to be associated with Alzheimer’s disease pathology, and prior work has shown associations between iron load and beta amyloid plaques. Quantitative susceptibility mapping (QSM) is a recently popularized MR technique to infer local tissue susceptibility secondary to the presence of iron as well as other minerals. Greater QSM values imply greater iron concentration in tissue. QSM has been used to study relationships between cerebral iron load and established markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 55 publications
4
78
2
Order By: Relevance
“…Consistently, previous research has confirmed that the susceptibility evaluated by QSM was positively correlated with chemically determined iron concentration in brain tissue, particularly in deep GM nuclei (16). Moreover, many studies indicated increased iron-related susceptibility in brain tissues, as assessed by QSM, in various neurological diseases, such as AD, PD, Huntington's Disease (HD), and amyotrophic lateral sclerosis (30)(31)(32)(33). Therefore, it is reliable to apply non-invasive QSM imaging to investigate the changes of iron content in deep GM nuclei for patients with long-term ACAS and PCAS.…”
Section: Discussionsupporting
confidence: 61%
“…Consistently, previous research has confirmed that the susceptibility evaluated by QSM was positively correlated with chemically determined iron concentration in brain tissue, particularly in deep GM nuclei (16). Moreover, many studies indicated increased iron-related susceptibility in brain tissues, as assessed by QSM, in various neurological diseases, such as AD, PD, Huntington's Disease (HD), and amyotrophic lateral sclerosis (30)(31)(32)(33). Therefore, it is reliable to apply non-invasive QSM imaging to investigate the changes of iron content in deep GM nuclei for patients with long-term ACAS and PCAS.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, by detecting the level of antioxidant protein in the hippocampus and amygdala, the level of oxidative stress in these two regions was found to be much higher than other regions. Moreover, the oxidative stress caused by iron accumulation will enhance the activity of IRP1, resulting in the enhancement of iron absorption through TfR1 and the increase in intracellular free iron level by reducing the concentration of ferritin-H and ferritin-L, which further enhances intracellular oxidative stress [93,98]. Based on magnetic resonance imaging (MRI) technology [99], it was found that iron accumulation may further lead to the deposition of Aβ amyloid and the formation of neurofibrillary tangles in the brain of AD patients.…”
Section: Effect Of Iron Metabolism Disorder On Admentioning
confidence: 99%
“…Studies evaluating the correlation between cognitive impairment in PD and the load of iron content [132,133] have identified that QSM increases covary with (1) MoCA scores in the hippocampus and thalamus; (2) poorer visual function and higher dementia risk scores in parietal, frontal, and medial occipital cortices; and (3) higher UPDRS-III scores in the putamen (all p < 0.05) [133]. QSM has also been used in AD [134], showing positive associations between susceptibility and amyloid PET in the pallidum and putamen, but with variable results regarding cortical areas. Overall, these findings suggest that QSM may be useful to track cognitive changes in PD; however, no studies analyzing patients with DLB are available [135].…”
Section: Biomarkers For Lewy Body Dementiasmentioning
confidence: 99%
“…SWI: Nigrosome 1 "swallow tail sign" differentiates DLB from AD with sensitivity (80%) [125]. QSM: Positive associations between susceptibility and amyloid PET in the pallidum and putamen of AD [134]. No studies in DLB.…”
Section: Neurophysiological Biomarkersmentioning
confidence: 99%